다양한 Ca/Al 주입비에서 Ca/Al-Cl LDH 형성에 의한 염소이온 제거 특성 - 김광덕; 송건호; 서승우; 오상화; 김홍태 (한국수처리학회지, 27(4), 2019)
Chloride removal rate by Ca-Al-Cl LDH precursor with several Ca:Al ratio was investigated. The LDH precursors were made of Ca(OH)2 and NaAlO2 for metal ions with 2 and 3 oxidant numbers, respectively. All experiments were conducted at 250 rpm for 2 hours at Jar Tester. The optimum equivalent ratio of Ca2+ and Al3+ was shown in the range of 2.8 to 4.2 where the maximum concentration (1.63 meq/L) of chloride was removed. The optimal dose of Ca(OH)2 and NaAlO2 to remove the maximum Cl- concentration was also investigated. The total dose of Ca2+ and Al3+ in milli-equivalent base at the optimal Ca2+/Al3+ ratio (3.32 meq/meq) was an important factor for Cl- removal. The Cl- removal was increased while the total dose increased to about 12 where the highest concentration of Cl- was removed by 2.23 meq/L. The solution pH was also depended on the total dose, showing the maximum value at the total dose of 12 meq similar pattern. It indicates that pH can be an important operaing factor for in-situ Cl- removal by Ca/Al-Cl LDH precursor. KCI Citation Count: 0